The Relationship of Parental Social Support and Self Control with Academic Procrastination in Students doing Online Learning during The Covid-19 Pandemic - Rachmasari, Alfi Aulia; Suroso; Pratitis, Niken Titi (Kirana Publisher (KNPub), 2025)
The covid 19 pandemic makes students have to take online learning, this causes students to feel bored and commit academic procrastination in doing assignments. Many factors cause academic procrastination, including parental social support and self-control. The purpose of this study was to determine the relationship of parental social support and self-control with academic procrastination in students doing online learning during the covid-19 pandemic both partially and together. This research method uses quantitative research methods with multiple regression data analysis techniques. The research variables were measured using an academic procrastination scale, a parental social support scale and a self-control scale. The research subjects were students at SMP Negeri 3 Luwuk who underwent online learning during the covid-19 pandemic with a total research sample of 113 out of 900 students with quota sampling technique. The results of multiple regression analysis show that parental social support and self-control together have a very significant correlation with academic procrastination.